Policy On The Development Of The Performance Of The Bima Regency Population And Civil Registration Service Employees: Nur Anilawati - nur anilawati; Khairul Sani (International Journal Of Humanities Education and Social Sciences (IJHESS), 2021)
As an effort to improve the performance of employees at the Department of Population and Civil Registration, Bima Regency must diagnose all factors that can improve performance and factors that can reduce employee performance, especially by knowing the challenges and obstacles faced by employees and by the institution itself. Therefore, it is very important for the Department of Population and Civil Registration, which has a low level of performance, to be able to anticipate it by involving employees in training and comparative studies (tour study) so that they have references in improving employee performance so that the public can feel exclusively the results of the employee's performance. The method is descriptive quantitative with a population of all employees and the public who receive services then the number of samples is 30 respondents random sampling. The results are 14.15% of respondents answered very satisfied, then 43.85 percent of respondents answered satisfied, and respondents who answered quite satisfied were 42.00% and respondents who answered dissatisfied 0.00%. This shows that the performance of the Department of Population and Civil Registration of Bima Regency needs to be improved, marked by the high number of respondents who answered quite satisfied, namely 42.00%.